2008
DOI: 10.3748/wjg.14.1463
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of reflux and eosinophilic esophagitis in two patients requiring different therapies: A review of the literature

Abstract: Eosinophilic esophagitis (EE) and gastroesophageal reflux disease (GERD) have overlapping clinical, manometric, endoscopic and histopathologic features. The diagnosis of EE is nowadays based upon the presence of 15 or more eosinophils per high power field (eo/HPF) in esophageal biopsies. We report the cases of two young males suffering from dysphagia and recurrent food impaction with reflux esophagitis and more than 20 eo/HPF in upper-mid esophagus biopsies, both of which became asymptomatic on proton pump inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
1
38
0
2
Order By: Relevance
“…Thus, based on our results, typical EoE, as strictly defined by unresponsiveness to PPI, may be rare in Japan, even among those who exhibit both typical endoscopic findings and histologically confirmed esophageal eosinophilia. However, recently, a substantial overlap of EoE and GERD has been documented in adult patients, and in a subset of these patients acid suppressive therapy with a PPI leads to symptom relief with endoscopic and histological resolution [11][12][13][14][15][16]. A mechanistic explanation for the therapeutic effect of PPIs is that the permeability of exogenous allergens to the esophageal wall is attenuated by the curing of the mucosal injury with acid suppression [22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, based on our results, typical EoE, as strictly defined by unresponsiveness to PPI, may be rare in Japan, even among those who exhibit both typical endoscopic findings and histologically confirmed esophageal eosinophilia. However, recently, a substantial overlap of EoE and GERD has been documented in adult patients, and in a subset of these patients acid suppressive therapy with a PPI leads to symptom relief with endoscopic and histological resolution [11][12][13][14][15][16]. A mechanistic explanation for the therapeutic effect of PPIs is that the permeability of exogenous allergens to the esophageal wall is attenuated by the curing of the mucosal injury with acid suppression [22].…”
Section: Discussionmentioning
confidence: 97%
“…However, a substantial overlap of EoE and gastroesophageal reflux disease (GERD) has been documented recently [11,12]. In addition, it has been shown that acid suppressive therapy with PPIs leads to symptom relief with endoscopic and histological resolution in some patients [13][14][15][16]. Consequently, in the clinical setting, there is a possibility that EoE is confused with GERD or given a diagnosis of refractory GERD in patients who are unresponsive to PPI treatment [10].…”
Section: Introductionmentioning
confidence: 97%
“…However, in a high percentage adult patients with eosinophilic infiltration in the esophagus present coexisting GERD (16) . This ratifies that the partial response to PPI does not exclude EoE diagnosis, and that pH monitoring and esophageal manometry should be performed in patients with atypical symptoms or when there is no diagnostic definition.…”
Section: Discussionmentioning
confidence: 99%
“…So, GERD and EoE coexist but are unrelated (16,23) . Correlation between pH monitoring and manometry findings There was no correlation between manometry and pH monitoring findings.…”
Section: Esophageal Manometrymentioning
confidence: 99%
“…A relação entre DRGE e EoE não está bem clara e sabe-se que as duas patologias podem coexistir ou contribuir para o aparecimento da outra (34).…”
Section:  Eliminação Dos Alimentos Baseado Em Testes Alérgicosunclassified